Professional Leadership Investigation in Big Data and Computer-Mediated Communication in Relation to the 11th Sustainable Development Goals (SDG) Global Blueprint - Aroba, Oluwasegun Julius (International Journal of Computing Sciences Research; Vol 8 (2024): Volume 8, 2024)
Purpose – This study aimed to explore how professionalism is impacted by big data and computer-mediated communication (CMC) in relation to level 5 leadership (L5LS). Methodology – The method adopted here is a research design and with the use of a quantitative research design approach to carry out the analysis, the study investigated the connection between leadership influence, communication satisfaction, and job satisfaction in the context of CMC. Convenience sampling was used to gather the data, and structured questionnaires were used to protect the privacy and identity of the participants. The association between employee engagement and CMC was examined using multiple regression analysis. Findings – The questionnaire used in this study also evaluated participants' perceptions of workplace leadership, their satisfaction with communication, and their job satisfaction with the 11 th Sustainable Development Goals. The results showed a gender distribution with a slight female preponderance among the 103 participants (48 men and 55 women). Furthermore, they indicated that computer-mediated communication (CMC) channels account for 65.4% of organizational communication. These results demonstrate the widespread adoption and utilization of information and communication technologies (ICTs) within the surveyed organizations. Practical Implication – The substantial presence of internet-based communication channels, representing 65.4% of organizational communication, emphasizes these channels' crucial role in facilitating effective communication within these organizations. Overall, the study analyses the effects of big data and CMC on professionalism and provides insights into gender distribution among participants. Research Limitations – Encouraging inclusive, safe, resilient, and sustainable cities and human settlements is the focus of Sustainable Development Goal (SDG) 11. Although it focuses on housing and urban challenges, its theoretical implications can be applied to several different sectors, such as professional leadership in big data. Theoretically, SDG 11 may have the following effects on Big Data-related professional leadership investigations.